Assessing the drinking water quality and performance of pond sand filters (PSF) in coastal area of Bangladesh: a cross sectional study on dacop upazila of Khulna - Alam, F M Ashraful; Islam, Md Shafiqul; Ghosh, Gopal Chandra; Yeasmin, Tania (International Journal of Advanced Geosciences, 2017)
The study focused on existing condition of drinking water and evaluates the performance of pond sand filters (PSFs) as a safe drinking water source of three selected Union of Dacope Upazila, Khulna in south-west coastal part of Bangladesh. This study exposed that the un-treated pond water is the main drinking water sources (54 %) in the study area. Other options for drinking water are PSF (43 %) and rain-water harvesting (RWH) systems (3%). The people who are using pond water directly as drinking water are suffered (67%) from various water-borne diseases in different times of the year. Most of the PSF users satisfied with the existing system of PSF. In most cases 85% the beneficiary’s willingness to pay for maintaining of PSFs. The water qualities were tested for the raw and treated water at various steps of the treatment process. The laboratory analysis showed that turbidity, pH, nitrate (NO3), ammonia (NH3), total dissolved solid (TDS), elec-trical conductivity (EC) and phosphate (PO4) of the PSFs water meet the Bangladesh standard, but the microbial contaminations are failed to meet the Bangladesh standard. In the raw water from three PSFs, the fecal coliform ranges are 64,122 and 136 CFU/100ml. After the treatment the fecal coliform ranges were 9, 19 and 38 CFU/100ml respectively. The outcome of the study provided information to ensure safe and adequate quantity of drinking water system in a disaster-prone coastal area of Bangladesh. It seems that if the PSF installs more in this region and takes action in regular monitoring and proper management, therefore, it will be one of the most sustainable drinking water sources for this coastal region.